2016
DOI: 10.5596/c16-007
|View full text |Cite
|
Sign up to set email alerts
|

Towards a new specialization in health librarianship: LGBTQ health

Abstract: In 1964, Canadian gay activist Jim Egan and Maclean’s journalist Sidney Katz decided to kick start a revolution (1). Katz’s 2-part article “The Homosexual Next Door: A Sober Appraisal of a New Social Phenomenon,” published by Maclean’s in February and March of that year (2, 3), was the first positive portrayal of homosexuality to appear in the Canadian mass media (4). Katz had worked closely with Egan on the milestone article, later recognised as lending critical mass to the nascent Canadian gay liberation mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…For instance, when it comes to understanding the quality and assessment of information that patients need in clinical settings, clinicians who lack the necessary research skills and expertise may rely on librarians to assist in disseminating information and guiding individuals in locating and understanding various resources either within or outside of the organization [ 54 ]. To best provide professional health information and act as effective liaisons, librarians must remain apprised of evidence-based subject knowledge, current medical trends, and health care policy, which can include outreach and partnerships to meet the needs of underserved, marginalized, or other groups with specialized needs [ 55 59 ]. A survey by Mi and Zhang, for example, indicated that 89.1% and 93.1% of HIP respondents acknowledged the importance of culturally competent library services and health sciences librarians, respectively, to ensure that library services and information were inclusive of and accessible to user groups across racial, linguistic, sexual, and other demographics [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, when it comes to understanding the quality and assessment of information that patients need in clinical settings, clinicians who lack the necessary research skills and expertise may rely on librarians to assist in disseminating information and guiding individuals in locating and understanding various resources either within or outside of the organization [ 54 ]. To best provide professional health information and act as effective liaisons, librarians must remain apprised of evidence-based subject knowledge, current medical trends, and health care policy, which can include outreach and partnerships to meet the needs of underserved, marginalized, or other groups with specialized needs [ 55 59 ]. A survey by Mi and Zhang, for example, indicated that 89.1% and 93.1% of HIP respondents acknowledged the importance of culturally competent library services and health sciences librarians, respectively, to ensure that library services and information were inclusive of and accessible to user groups across racial, linguistic, sexual, and other demographics [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Disparities can be specific to sub-groups under the broader LGBTQ+ umbrella and vary based on other intersecting, contextual, and identity-related aspects [1][2][4][5]. A key factor contributing to these health challenges is informational, as LGBTQ+ people may experience difficulty learning about their healthcare needs, navigating the healthcare system, and addressing barriers to care [6][7]. Despite the significance of information in shaping LGBTQ+ health outcomes, few studies investigate LGBTQ+ health from an informational perspective.…”
Section: Introductionmentioning
confidence: 99%
“…After an extensive review of the literature, the authors found no works focusing on medical collection development for the LGBTQIA population in academic libraries in the United States. Only a few studies since the early 2000s have covered the health science information needs of the LGBTQIA community in North America (Fikar and Keith 2004;Flemming and Sullivant 2000;Morris and Hawkins 2016;Roberto 2014, 2016;Perry 2001). There is a certain irony to this as a citation analysis of the scholarly literature of LGBT studies by Antell (2012) found that the field has a high rate of interdisciplinary citations and cites particularly heavily from medical journals and books.…”
Section: Literature Reviewmentioning
confidence: 99%